Formula feeding practice among mothers with infants aged 0–5 months in Afghanistan: prevalence and associated factors - Stanikzai, Muhammad Haroon; Tawfiq, Essa; Ezadi, Zainab; Jafari, Massoma; Dadras, Fateme; Sayam, Hadia; Dadras, Omid (Springer Science and Business Media LLC, 2026)
Exclusive breastfeeding is vital for infant health, yet reliance on formula feeding is rising globally. In Afghanistan, evidence on the prevalence and determinants of formula feeding is limited. This study aimed to estimate the prevalence of formula feeding among infants aged 0-5 months and to identify associated factors. This study utilized data from the 2022-2023 Afghanistan Multiple Indicator Cluster Survey (MICS), including 3,873 weighted mother-infant dyads. The outcome variable in this study was any formula feeding, defined as the proportion of infants aged 0-5 months who were fed formula in the past 24 h. Bivariate and multivariable logistic regression analyses were employed to identify factors associated with formula feeding. The prevalence of formula feeding was 9.2% (95%CI: 7.6-10.8%). The likelihood of infant formula feeding was significantly higher in infants aged 4-5 months (AOR = 1.59, 95%CI: 1.01-2.53); in infants who received prelacteal feeding (AOR = 1.94, 95%CI: 1.38-2.72); in infants whose mothers were aged 30-39 years (AOR = 1.46, 95%CI: 1.00-2.12); in infants from the Southern East (AOR = 4.59, 95%CI: 2.40-8.76), South (AOR = 2.35, 95%CI: 1.15-4.81) and West (AOR = 3.71, 95%CI: 1.57-8.76) regions. Nearly one in ten Afghan infants under six months are formula-fed. Interventions, particularly those addressing prelacteal feeding and region-specific vulnerabilities, are needed to safeguard exclusive breastfeeding and improve infant nutrition in Afghanistan.